47.2k views
0 votes
Show all work to solve the equation for x. If a solution is extraneous, be sure to identify it in your final answer. √(x-3)+5=x.

User Dylan B
by
7.1k points

1 Answer

3 votes

Final answer:

To solve \(\sqrt{(x-3)}+5=x\), we isolate \(x\), square both sides, obtain a quadratic equation, factor it, and find the solutions \(x = 4\) and \(x = 7\), of which \(x = 4\) is extraneous and \(x = 7\) is the correct solution.

Step-by-step explanation:

To solve the equation \(\sqrt{(x-3)}+5=x\) for x, we will perform operations step by step to isolate x. First, we move all terms containing x to one side and the constant terms to the other side.

Subtract 5 from both sides: \(\sqrt{(x-3)} = x - 5\)Square both sides to eliminate the square root: \((\sqrt{(x-3)})^2 = (x - 5)^2\)Expand the right side using the FOIL method: \(x-3 = x^2 - 10x + 25\)Rearrange the equation to form a quadratic equation: \(0 = x^2 - 11x + 28\)Factor the quadratic equation: \(0 = (x - 4)(x - 7)\)Solve for x by setting each factor equal to zero: Check each potential solution in the original equation to verify whether each or is an extraneous solution.

Plugging x = 4 into the original equation, we get \(\sqrt{(4-3)}+5 = 4\), which simplifies to \(1 + 5 = 4\), which is not true, so x = 4 is an extraneous solution.

Plugging x = 7 into the original equation, we get \(\sqrt{(7-3)}+5 = 7\), which simplifies to \(2 + 5 = 7\), which is true, so x = 7 is the correct solution.

User Akalenuk
by
7.8k points